#### Answer

$\dfrac{2y^{5/7}}{3}$

#### Work Step by Step

$\dfrac{2}{3y^{-(5/7)}}=\dfrac{2}{\frac{3}{y^{5/7}}}=\dfrac{2y^{5/7}}{3}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\dfrac{2y^{5/7}}{3}$

$\dfrac{2}{3y^{-(5/7)}}=\dfrac{2}{\frac{3}{y^{5/7}}}=\dfrac{2y^{5/7}}{3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.